Notes on Early Land Plants Today. 59. Leptolejeunea himalayensis and Leptocolea mirpurensis (Marchantiophyta, Lejeuneaceae) synonymous with Lejeunea cocoes and Cololejeunea raduliloba, respectively - Shu, Lei; Zhu, Rui-Liang (Phytotaxa, 2014)
Lejeuneaceae is the largest family of the liverworts with about 1700 currently accepted species (He & Zhu 2011, He et al. 2012), but some of them are poorly known and their status is still unclear. Leptolejeunea himalayensis Pandé & Misra (1943: 168) is known only from India and previously suspected of belonging to one member of Lejeunea Libert (1820: 372) (Awasthi 1986). Leptocolea mirpurensis Khan (1957: 23) from Bangladesh has never been studied since its first description in 1957. Although the types of the two taxa were not available for our study, the original description and illustrations (Pandé & Misra 1943, Khan 1957) undoubtedly indicate that Leptolejeunea himalayensis and Leptocolea mirpurensis are conspecific with Lejeunea cocoes Mitten (1861: 114) and Cololejeunea raduliloba Stephani (1895: 251), respectively. Lejeunea cocoes has been reported for India (Singh & Nath 2007, Manju et al. 2012), and is also known in China, Indonesia, Malaysia, Papua New Guinea, and Sri Lanka (So & Zhu 1998, Zhu & So 2001, Lee 2013), furthermore from Chagos, Diego Garcia (Seaward et al. 2006) and from the Fiji Islands (Pócs et al. 2013). Cololejeunea raduliloba, a paleotropical species (Zhu & So 2001), is newly reported for Bangladesh.